Estrus response and fertility rate in Kundhi buffaloes following estrus synchronization in breeding season - Kalwar, Qudratullah; AhmedMemon, Akeel; Bhutto, Muhammad Bachal; Kunbhar, Hamzo Khan; Mirani, Amjad Hussain; Anwar, Muhammad; AhmedWagan, Shakeel (Journal of Advanced Veterinary and Animal Research, 2015)
The aim of the present study was to compare the effect of two estrus synchronization treatments i.e., Ovsynch alone and Ovsynch plus Controlled Internal Drug Release (CIDR), on the occurrence of estrus and conception rate in Kundhi buffalo during breeding season in Pakistan. Forty Kundhi buffaloes were randomly selected and were divided into three groups; Group A (n=16; Ovsynch) received 2 mL GnRH intramuscularly (i/m) on day 0 and 9. On day 7, 5 mL prostaglandin F2? (PGF2? analogue) was administered through i/m route. The buffaloes of Group B (n=17; Ovsynch+CIDR) received 2 mL GnRH on day 0 along with implantation of CIDR. On day 7, the CIDR was removed, and 5 mL PGF2? analogue was injected through i/m route. A second dose of GnRH was administered through i/m route after 48 h of PGF2? inj. in both groups. Group C (n=7; control) received 2 mL normal saline through i/m route on day 0, 7 and 9. The buffaloes of all three groups were artificially inseminated twice (12 h and 24 h after the second GnRH inj.) using frozen-thawed semen. Estrus response differed significantly (P<0.05) among the groups. The animals of Group B (76.47%) showed superior estrus response as compared to others. Higher conception rate (52.94%) was observed in the animals of Group B; however, the difference was not significant. In conclusion, Ovsynch+CIDR causes to occur better estrus response and conception rate as compared to Ovsynch alone in Kundhi buffaloes during breeding season. http://dx.doi.org/10.5455/javar.2015.b97